Effects of exogenous deoxyribonuclease I in collagen antibody-induced arthritis - Kristína Macáková; Veronika Borbélyová; Mária Tekeľová; Jakub Janko; Michal Pastorek; Richard Hokša; Norbert Moravanský; Emöke Šteňová; Barbora Vlková; Peter Celec (BMC, 2024)
Abstract Background Rheumatoid arthritis (RA) is associated with a high concentration of extracellular DNA (ecDNA). This could be a consequence of the inflammation, but the ecDNA could also be involved in the unknown etiopathogenesis of RA. Clearance of ecDNA is hypothesized to prevent the development of RA. This study aimed to analyze the effects of exogenous deoxyribonuclease I (DNase I) administration in an animal model of RA. Methods The collagen antibody-induced arthritis (CAIA) model of RA was induced in adult female DBA/1J mice. CAIA mice were treated with saline or DNase I (10 mg/kg) every 12 h for the whole duration of the experiment. Arthritic scores were assessed. Paw volume and temperature were assessed using a plethysmometer and a thermal camera, respectively. Plasma ecDNA and its subcellular origin were analyzed using fluorometry and real-time PCR. DNase activity was quantified with single radial enzyme diffusion method. Results The CAIA model was successfully induced as proved by a higher volume, temperature and the overall arthritis score in comparison to controls. The administration of DNase I resulted in a nearly two-fold increase in serum DNase activity. Still, it did affect neither plasma ecDNA, nor the arthritis score or other measures of joint inflammation. Conclusion Our results suggest that exogenous DNase I does not prevent the development of CAIA in mice. Whether this is true for other animal models of arthritis or clinical RA requires further research. EcDNA does not seem to be involved in the pathogenesis of CAIA. Additional studies are also needed to elucidate the role of ecDNA in the development of RA, focusing especially on its origin and inhibition of ecDNA release.